Pengetahuan Penatalaksanaan Dismenore Remaja Putri - Elsera, Chori; Wulan Agustina, Nur; Sat Titi Hamranani, Sri; Nur Aini, Anisa (INVOLUSI: Jurnal Ilmu Kebidanan, 2022)
Dysmenorrhea is pain during menstruation in the lower abdomen that radiates to the waist which can be accompanied by headaches that last until menstruation ends, which is characterized by emotional changes, difficulty sleeping, disturbed activities and difficulty concentrating. Based on data from the Profile of the Central Java Provincial Health Office in 2017, the number of young women aged 10-19 years was 2,899,120 people. Meanwhile, those experiencing dysmenorrhea reached 1,465,876 people. The purpose of this study was to determine the characteristics of the respondents and to describe the knowledge of young women in overcoming dysmenorrhea. This research design is a quantitative descriptive study. This study was conducted to describe the knowledge of adolescent girls in overcoming dysmenorrhea. The sampling technique in this research is purposive sampling. The sample in this study was 98 young women. The instrument used in this research is a questionnaire and analyzed using unvariate analysis. The results of the study of Knowledge of Adolescent girls in overcoming dysmenorrhea at SMP N 4 Klaten obtained the average age of 14 years ± SD (.44907), Knowledge of how to overcome dysmenorrhea was good as many as 77 (78.6%) students, Enough 17 students (17.3 %), Less 4 students (4.1%). The implication of this research is that knowledge on how to overcome dysmenorrhea needs to be socialized from an early age so that the problem of dysmenorrhea can be addressed immediately.